Mitochondria-targeting Cu₃VS₄ nanostructure with high copper ionic mobility for photothermoelectric therapy - Dong, Yushan (2024)
Thermoelectric therapy has emerged as a promising treatment strategy for oncology, but it is still limited by the low thermoelectric catalytic efficiency at human body temperature and the inevitable tumor thermotolerance. We present a photothermoelectric therapy (PTET) strategy based on triphenylphosphine-functionalized Cu3VS4 nanoparticles (CVS NPs) with high copper ionic mobility at room temperature. Under near-infrared laser irradiation, CVS NPs not only generate hyperthermia to ablate tumor cells but also catalytically yield superoxide radicals and induce endogenous NADH oxidation through the Seebeck effect. Notably, CVS NPs can accumulate inside mitochondria and deplete NADH, reducing ATP synthesis by competitively inhibiting the function of complex I, thereby down-regulating the expression of heat shock proteins to relieve tumor thermotolerance. Both in vitro and in vivo results show notable tumor suppression efficacy, indicating that the concept of integrating PTET and mitochondrial metabolism modulation is highly feasible and offers a translational promise for realizing precise and efficient cancer treatment.